Legal Protection Of Workers Rights In Time Work Agreements Based On Labor Law - Masitah Pohan (International Journal of Society and Law, 2024)
Labor​ is the main factor in A company Where worker that's what it is bone back driving force wheel company and already appropriate workers​ get proper reward, agreement​ is something deed with Name one person or more tie himself to someone else or deeper​​ the shape agreement That is something Suite containing words​ promises. Pe l ne l litian This me l nge l know l i challenge​​ How implementation agreement for worker time certain in Constitution Number 13 of 2003. Me l tode l pe l ne l litian This de l only I 'm waiting for me to eat stu l in Pu l staka with types and approaches study law empirica, nature research used​ nature descriptive, data source used is primary data sources with do interview to sources and secondary data sources consisting of from material law tertiary. Deep data collection tools study This is studies field and study literature as well as use qualitative data analysis. Based on results study understood that Law No.13 of 2003 article I paragraph I – 4 stipulates that in The law in question with employment is all all related things​ with power work on time before, during and after the work period company, pawn shop refers to existing laws / regulations​ determined by the government, regulations companies and deals with employees​ responsible answer and at once protect rights worker including field welfare is a must noticed company.